Preliminary bird survey in human settlements near Taman Negara Kuala Tahan, Jerantut, Pahang - Shaikh Nasir, Nur Thabitah; Musa, Nor Lailatul Wahidah; Nawi, Liliwirianis; Md Isa, Nurun Nadhirah; Mohd Jan, Sarah Laila (GADING Journal of Science and Technology, 2024)
Birds respond actively to changes in environmental conditions. Deforestation and habitat fragmentation due to land use cause the loss of bird species diversity and changes in bird community, thus altering the feeding guilds that are important for many ecosystem services. The objectives of this study were to determine the avian species found in human settlements near Taman Negara Kuala Tahan and to categorise the observed bird species into feeding guilds. Bird surveys were conducted via binoculars using point count (PC) and opportunistic count (OC) methods for three days in early September 2022. A total of 179 individuals across 30 species from 13 families were recorded in the observed areas with Pycnonotidae having the highest number of species (7 species), followed by Columbidae (5 species) and Nectariniidae (4 species). Bird species with the highest number of individuals was Passer montanus (36 individuals) and the most found species was Copsychus saularis (20 out of 23 PC points). Six feeding guilds were also determined with insectivores and frugivores being the two most common feeding guilds found with 19 and 17 species, respectively. Out of the 30 species found, one is listed as Near Threatened, three as Vulnerable, and one as Endangered. Bird biodiversity must be considered when developing areas adjacent to rainforests to sustain local bird populations.